Short Interest and Aggregate Stock Returns: International Evidence - Gorbenko, Arseny (The Review of Asset Pricing Studies, 2023)
Abstract I find that short interest significantly and negatively predicts aggregate stock returns in 24 of 32 countries examined. This predictability survives out-of-sample tests, persists outside of recessions, and is not subsumed by other well-known return predictors. The results indicate that short interest contains valuable information for forecasting international market returns that is distinct and more powerful than that of other available predictors. However, the predictive power of short interest varies over time and across regions. It is higher around economic downturns when margin requirements tighten and in regions where short selling is constrained by regulations or equity lending market frictions. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.